PENGARUH PERSAINGAN, DISTRIBUSI DAN PROMOSI TERHADAP KINERJA PELAKU USAHA MIKRO KECIL DAN MENENGAH (UMKM) KERIPIK DI DESA KARANG ANYAR DELI SERDANG - Wansyah Prayogi, Anggi; Utama, Indra; Yuliana, Yayuk; Harahap, Nur'ain (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2024)
This study aims to analyze the Influence of Competition, Distribution and Promotion on the Performance of Micro, Small and Medium Enterprises (MSMEs) of Chips in Karang Anyar Village, Deli Serdang. The population in this study were all MSMEs of Chips in Karang Anyar Village, Deli Serdang, totaling 44. The sampling technique in this study applied the saturated sample method. Since the number of MSMEs of Chips in Karang Anyar Village, Deli Serdang was 44 MSMEs (less than 100), all MSMEs of Chips in Karang Anyar Village, Deli Serdang were taken as research objects. The use of analysis methods, namely Validity Test and Reliability Test, Classical Assumption Test, Multiple Regression Analysis, t-Test, F-Test and Determination Coefficient. The findings with partial show that competition has a real and positive influence on the performance of MSMEs of Chips in Karang Anyar Village, Deli Serdang. Distribution has a real influence on the performance of MSMEs of Chips in Karang Anyar Village, Deli Serdang. Promotion has a real influence on the performance of UMKM Keripik actors in the village. From the simultaneous results of the study, it is proven that competition, distribution and promotion on the performance of UMKM Keripik actors in the village. The relevant determination coefficient value (R Square) is 0.617 or 61.7% of the dependent variable can be described through the independent variable and the remaining results are described from other variables outside the variables being viewed